Macroeconomic effects of artificial intelligence on emerging economies: Insights from Bangladesh - Provash Kumer Sarker (Economics, Management and Sustainability)
Artificial intelligence (AI) has the potential to increase economic growth substantially across the world. This paper explores the predicted potentials of AI from macroeconomic perspectives, employing theoretical analysis and contextualizing Bangladesh. The study employs time series data to examine the effects of AI on the labor market and productivity. The findings indicate that Bangladesh was yet to realize the expected economic merits though the integrated number of AI-induced industry robots has been insignificant. For AI to be effective in Bangladesh, the country shall adopt more AI robots across the various sectors, mainly manufacturing and service. Besides, the country may complement the human labor force with AI labor instead of relying on only one as a source of labor.